Green synthesis of carbon dot structures from Rheum Ribes and Schottky diode fabrication - Durmus, Muhammed Taha; Bozkurt, Ebru (Beilstein Journal of Nanotechnology, 2024)
In this study, we aimed to synthesize new carbon dot structures (CDs) in a single step by using the plant Rheum Ribes for the first time and to contribute to the studies in the field of diode fabrication by using the new CDs. The CDs were obtained by hydrothermal synthesis, which is commonly used in the literature. TEM and zeta potential measurements were used to determine morphology and sizes of the CDs, and XRD, XPS, and FTIR and micro-Raman spectroscopy were used for structural characterization. Optical characterization of the CDs was done by absorption and steady-state fluorescence measurements. In the second part of the study, CDs were dripped onto silicon substrates, and a CDs thin film was formed by evaporation. A diode structure was obtained by evaporating gold with the shadow mask technique on the CDs film, and the current–voltage characteristics of this diode were examined. The synthesized CDs are spherical with an average size of 5.5 nm, have a negative surface charge and contain 73.3 atom % C, 24.0 atom % O, and 2.7 atom % N. The CDs exhibit fluorescence at approximately 394 nm. The layer thickness and bandgap energy of the prepared CDs film were calculated as 566 nm and 5.25 eV, respectively. The ideality factor and the measured barrier height (Φb) of the CDs-based Schottky diode were calculated as 9.1 and 0.364 eV, respectively. The CDs were used as semiconductor material in a Schottky diode, and the diode exhibited rectification behavior. The results obtained from this study showed that CDs can be applied in the field of electronics, apart from sensor studies, which are common application areas.
Keywords: carbon dot (CD) structures; green synthesis; Rheum Ribes plant; Schottky diode